Modulación de la expresión de E-Cadherina por Glipicano-3 en cáncer de mama humano - Lugones, Ana Clara (2022)
Breast cancer is one of the diseases with the greatest impact on world health, metastasis being the main cause of death. To metastasize, carcinoma cells must reactivate a latent embryonic program called the epithelial-mesenchymal transition (EMT). Glypican-3 (GPC3) is a member of the heparin sulphate proteoglycan family that is bound to the plasma membrane and plays an important role in embryonic development. However, its expression is lost in most adult tissues, except for some such as the mammary gland. It has been involved in the regulation of proliferation and survival, which is why it has been linked to cancer.\nIn the first place, through comparative studies of the expression of this glypican, it is shown that normal breast tissue presents high levels of GPC3, and that these levels decrease in the different tumor types, mainly in the basal like subtype. Its effect on differential gene expression was also studied. Then we proposed to analyze in depth the role of the glypican in EMT traversed by mammary tumor cells, focusing on its molecular and cellular mechanisms of action. For this purpose, we used human breast cancer cell lines genetically modified previously by our group. Thus, the expression of GPC3 was silenced in MCF-7 cells, whereas this glypican was overexpressed in MDA-MB231 cells. Using these sublines, we observed that cells expressing GPC3 exhibit a more epithelial phenotype. By evaluating cell adhesion to matrix components, we determined that GPC3 silencing did not cause changes in MCF-7 cell adhesion to FN and plastic, but reduced their adhesion to LN. On the other hand, the overexpression of GPC3 in MDA-MB231 cells induced a decrease in their ability to adhere to FN and LN, as well as to plastic. We analyzed the expression of adhesion proteins by WB and although we did not find important changes in the MCF-7 sublines, the MDA-MB231-GPC3 cells exhibited lower levels of ?1 and ?4 integrins. On the other hand, when studying markers and molecules associated with EMT, we found that GPC3 silencing increased the mesenchymal characteristics of MCF-7 cells, decreasing the expression of the epithelial marker E-Cadherin. The overexpression of GPC3 in MDA-MB231 cells induced the E-Cadherin re-expression and decreased the mesenchymal marker Vimentin. We also show that the E-Cadherin transcriptional repressor ZEB1 is up-regulated in MCF-7 cells with silenced GPC3, while it is down-regulated in MDA-MB231-GPC3 cells. Although no changes were found in the levels of the transcription factor SNAI1 in the MCF7 sublines, they increased in the MDA-MB231-GPC3 cells. When analyzing the effect of GPC3 on the signaling pathways involved in the regulation of EMT, we found that cells expressing this glypican exhibit lower Smad2/3 phosphorylation, suggesting a lower activation of the TGF-? pathway. Also, supporting previous results from our group, we observed GPC3 induces activation of the non-canonical Wnt pathway while inhibiting the canonical pathway. Bioinformatic enrichment analyzes where gene signatures associated with the previous processes and pathways were studied supported the results obtained. Finally, we show that patients whose primary tumors have higher levels of GPC3 have a higher SLE and a lower probability of relapse. These results suggest the usefulness of GPC3 as a prognostic biomarker capable of predicting the patient outcome. Our data indicate that GPC3 is an important regulator of EMT in breast cancer and a potential target for the treatment of metastasis.